Operation of a UXE-Type 11-Level Inverter with Voltage-Balance Modulation Using NLC and ACO-Based SHE - Mohammad Ali (Sustainability, 2021)
In this article, the UXE-Type inverter is considered for eleven-level operation. This topology exhibits a boosting capability along with reduced switches and one source. An algorithm that utilizes the redundant states to control the voltage-balance of the auxiliary direct current (DC)-link is presented. The proposed control algorithm is capable of maintaining the voltages of each capacitor at <semantics>Vdc/4</semantics> resulting in a successful multilevel operation for all values of load. The inverter is also compared with 11-level inverters. The modulation of the inverter is performed by employing nearest level control and ant colony optimization based selective harmonic elimination. The maximum inverter efficiency is 98.1% and its performance is validated on an hardware-in-the-loop platform.